Estudo e Implementação de Algoritmos de Agrupamento e de Rotulação Aplicados no Diagnóstico por Imagens de Patologias Renais - Basílio, Arthur; da Silva, Pedro; Machado, Vinícius; Aldemann, Nayze (Proceedings of the Regional School on Computing of Ceará, Maranhão, and Piauí (ERCEMAPI), 2020)
This article proposes the application of clustering and labeling algorithms to aid in the diagnosis of renal pathologies. The information is extracted from the renal images provided in conjunction with the database containing nephrology diagnostic records. Through unsupervised learning algorithms, different groups are formed. Through the labeling algorithm, the main attributes that characterize each group are revealed, facilitating their understanding. The article also demonstrates the influence of such information extracted from the images, as well as the aid in the knowledge acquisition process promoted by the grouping and labeling.